AUTOMATION OF THE GREASE APPLY PROCESS TO IMPROVE THE EFFICIENCY OF USING GREASE LINE SUB ASSY PAD COMP - Aulia, Hani Aulia Lejaringtyas; Fatkhurrozi , Bagus; Kurniawan , Andriyatna Agung (TESLA: Jurnal Teknik Elektro, 2024)
One aspect that needs to be paid attention to in the manufacturing industry in order to produce goods with guaranteed quality is the final process. This process is an assembly process. One of the parts that goes through the assembling process is the caliper. The caliper is an important component in disc brakes which functions to clamp the brake lining (pad comp) to the disc disc area and also to support the brake lining (pad comp) and brake piston. This comp pad will then press the disc disc so that it will create friction to stop the rotation of the disc brake. The comp pad must work optimally to be able to stop the disc brake rotation. In order for the comp pad to work optimally, it requires dampening material in the form of grease with the right quality and quantity. The applied volume of grease on the comp pad must comply with the standards for each type of comp pad. Apart from that, grease should not get on the front of the comp pad (lining) because that will make the product Not Good (NG). Therefore, an automatic grease application tool was created to increase the efficiency of grease use and the grease volume on the comp pad can be stable according to the requirements. with standards and there is no process of applying grease to parts where it is not supposed to. With this tool, the percentage of grease usage efficiency for the inner area is 0.5% and for the outer part it is 2.55%. Apart from that, there is no longer a process of applying grease to parts where it shouldn't be Abstrak Salah satu aspek yang perlu diperhatikan pada industri manufaktur agar menghasilkan barang dengan kualitas terjamin adalah pada proses terakhir. Proses tersebut adalah proses perakitan (assembling). Salah satu part yang melalui proses assembling adalah caliper. Caliper adalah komponen penting pada rem cakram yang berfungsi untuk menjepit kampas rem (pad comp) pada daerah piringan cakram dan juga untuk menopang kampas rem (pad comp) dan piston brake. Pad comp ini nantinya akan menekan bagian piringan cakram sehingga akan menimbulkan gesekan untuk menghentikan putaran rem cakram. Pad comp harus bekerja secara optimal supaya mampu menghentikan putaran rem cakram. Agar pad comp dapat bekerja dengan optimal, diperlukan adanya bahan peredam berupa grease dengan kualitas dan kuantitas yang tepat. Volume apply grese pada pad comp harus sesuai dengan standar masing-masing jenis pad comp. Selain itu, grease juga tidak boleh terkena pada bagian depan pad comp (lining) karena itu akan membuat produk menjadi Not Good (NG) Maka dari itu, dibuatlah alat apply grease otomatis untuk meningkatkan efisiensi pemakaian grease dan volume grease pada pad comp bisa stabil sesuai dengan standarnya serta tidak ada proses apply grease ke bagian yang tidak seharusnya. Dengan adanya alat ini, diperoleh persentase efisiensi pemakaian grease untuk inner sebesar 0,5% dan untuk outer sebesar 2,55%. Selain itu, tidak ada lagi proses apply grease ke bagian yang tidak semestinya